Courts of the constitution. - Cox, Archibald (New Delhi, 1992)
Two centuries age the framers of the constitution of the United State of America outlined a unique structure of government. There majestic phrases fix limits and evoke historic ideals.
Keywords: United States -Constitutional law -Interpretation and co